2018
DOI: 10.1177/0963721417729036
|View full text |Cite
|
Sign up to set email alerts
|

A Social Safety Net: Developing a Model of Social-Support Figures as Prepared Safety Stimuli

Abstract: Although the presence of social-support figures (e.g., close friends and family members) is known to increase feelings of safety, reduce threat responses, and improve health, the route by which these effects occur is not well understood. One explanation is that social-support figures are members of a powerful category of safety signals—prepared safety stimuli. Here, we review research demonstrating that social-support figures act as prepared safety stimuli and explore the impact that these unique safety stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 37 publications
6
65
1
Order By: Relevance
“…Moreover, this effect is specific to attachment figures because it was not observed to the same extent as thinking of a positive non-attachment representation. This finding supports one recent model that attachment cues represent unique safety signals that constrain fear learning (Hornstein and Eisenberger, 2018 ). These results are consistent with evidence that attachment primes inhibit the fear system at neural (Coan et al, 2006 ), physiological (Bryant and Chan, 2015 ) and subjective (Ditzen et al, 2008 ) levels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, this effect is specific to attachment figures because it was not observed to the same extent as thinking of a positive non-attachment representation. This finding supports one recent model that attachment cues represent unique safety signals that constrain fear learning (Hornstein and Eisenberger, 2018 ). These results are consistent with evidence that attachment primes inhibit the fear system at neural (Coan et al, 2006 ), physiological (Bryant and Chan, 2015 ) and subjective (Ditzen et al, 2008 ) levels.…”
Section: Discussionsupporting
confidence: 89%
“…On the basis of these findings, a model has been proposed in which social supports serve as a ‘unique’ safety signal that inhibits fear responses (Hornstein and Eisenberger, 2018 ). They are unique in that they require no prior training and can lead to long-term reductions of fear, unlike conditioned inhibitors.…”
mentioning
confidence: 99%
“…These can provide a needed context for change and growth enabling the client to develop the courage to explore difficult and frightening material (Holmes, ; Holmes & Slade, ; Knox, ; Mearns & Cooper, ). Hornstein and Eisenberger () reviewed the evidence that the presence of ‘support and safety figures’ impacts both fear acquisitive and extinction. Engaging stressors with ‘supportive others’ verses alone impacts the physiological response to the stressor.…”
Section: Social Mentalities and Social Needsmentioning
confidence: 99%
“…It has been demonstrated that social-support-figure stimuli act as prepared safety stimuli, such that without requiring specific safety training, social-support-figure stimuli are less readily associated with fear and inhibit fear responding (Hornstein et al, 2016). More specifically with regard to fear extinction, this work has shown that, without any safety training, the presence of socialsupport-figure images enhanced extinction of learnedfear responses for other cues, leading to continued inhibition of the fear response once the social-supportfigure image was removed (Hornstein et al, 2016). These findings contrast sharply with canonical knowledge of learned-safety signals, which require safety training, lead to return of fear once removed, and prevent fear extinction (Lovibond et al, 2000;Rescorla, 1969Rescorla, , 1971Rescorla, , 2003.…”
mentioning
confidence: 99%